Stress and the Emerging Roles of Chromatin Remodeling in Signal Integration and Stable Transmission of Reversible Phenotypes - Weaver, Ian C. G.; Korgan, Austin C.; Lee, Kristen; Wheeler, Ryan V.; Hundert, Amos S.; Goguen, Donna (Frontiers in Behavioral Neuroscience, 2017)
The influence of early life experience and degree of parental-infant attachment on emotional development in children and adolescents has been comprehensively studied. Structural and mechanistic insight into the biological foundation and maintenance of mammalian defensive systems (metabolic, immune, nervous and behavioral) is slowly advancing through the emerging field of developmental molecular (epi)genetics. Initial evidence revealed that differential nurture early in life generates stable differences in offspring hypothalamic-pituitary-adrenal (HPA) regulation, in part, through chromatin remodeling and changes in DNA methylation of specific genes expressed in the brain, revealing physical, biochemical and molecular paths for the epidemiological concept of gene-environment interactions. Herein, a primary molecular mechanism underpinning the early developmental programming and lifelong maintenance of defensive (emotional) responses in the offspring is the alteration of chromatin domains of specific genomic regions from a condensed state (heterochromatin) to a transcriptionally accessible state (euchromatin). Conversely, DNA methylation promotes the formation of heterochromatin, which is essential for gene silencing, genomic integrity and chromosome segregation. Therefore, inter-individual differences in chromatin modifications and DNA methylation marks hold great potential for assessing the impact of both early life experience and effectiveness of intervention programs—from guided psychosocial strategies focused on changing behavior to pharmacological treatments that target chromatin remodeling and DNA methylation enzymes to dietary approaches that alter cellular pools of metabolic intermediates and methyl donors to affect nutrient bioavailability and metabolism. In this review, we discuss the potential molecular mechanism(s) of gene regulation associated with chromatin modeling and programming of endocrine (e.g., HPA and metabolic or cardiovascular) and behavioral (e.g., fearfulness, vigilance) responses to stress, including alterations in DNA methylation and the role of DNA repair machinery. From parental history (e.g., drugs, housing, illness, nutrition, socialization) to maternal-offspring exchanges of nutrition, microbiota, antibodies and stimulation, the nature of nurture provides not only mechanistic insight into how experiences propagate from external to internal variables, but also identifies a composite therapeutic target, chromatin modeling, for gestational/prenatal stress, adolescent anxiety/depression and adult-onset neuropsychiatric disease.